Pulse crops research in India - ASTHANA, A N (The Indian Journal of Agricultural Sciences, 2013)
India grows such a variety of pulse crops which none of the countries in the world grows. Though the area underpulses has been fluctuating between 22 and 24 million ha, an improvement in production and productivity was 12.42million tonnes and 520 kg/haduring 1964-65 to 14.12 million tonnes and 609 kg/ha during 1994-95 during to developmentof new varieties and technologies. Special features, and areas of adoption of varieties of different pulse crops in differentregions of the country are given consisely. Total germplasm collection, evaluation and conservation under All-India Coordinated Pulses Improvement Project are also highlighted. Future thrust areas are also suggested in respect of geneticenhancement of yield and grain quality, cropping systems research, integrated nutrient and drought, water and pest management.